Paysage et risques naturels. Quelles perspectives pour l’adaptation du littoral au changement climatique ? - Charlotte Gustave Huteau (Développement Durable et Territoires)
Adaptation to climate change, as well as human settlement impact the landscape. On coastal areas, the landscape is likely to be impacted by erosion and rising sea levels.This raises the issue of how this concept of landscape can be used to convert some territories at risk, particularly to make certain measures more acceptable for the populations, or to propose innovative solutions.It appears that the notion of risk, and of landscape, have many connections that would be interesting to exploit in order to further consider the landscape in this context. This could help stakeholders to think differently about spatial recomposition of these territories.